The freshwater molluscs of Serbia: Annotated checklist with remarks on distribution and protection status - Marković, Vanja; Gojšina, Vukašin; Novaković, Boris; Božanić, Milenka; Stojanović, Katarina; Karan-Žnidaršič, Tamara; Živić, Ivana (Zootaxa, 2021)
We present a checklist of 86 valid freshwater mollusc species of Serbia (65 gastropods and 21 bivalves) belonging to 19 families (15 gastropods and four bivalves). The list is based on our latest research and includes data from published sources and personal communications. The most diverse family among gastropods is Planorbidae (16 species), while Sphaeriidae are most diverse within the bivalves (10 species). Ten species are local endemics (all of them gastropods), while eight are introduced species (three gastropods and five bivalves). The Danube River and its smaller tributaries harbour the most diverse gastropod community, with a total of 61 species (41 gastropods and 20 bivalves). The snail Theodoxus transversalis (Pfeiffer, 1828) and the bivalve Unio crassus Philipson, 1788 are listed as EN (endangered) on the global (IUCN) level, while the snail Plagigeyeria gladilini Kuščer, 1937 and the bivalves Pseudanodonta complanata (Rossmässler, 1835) and Sphaerium rivicola (Lamarck, 1818) are considered as VU (vulnerable) species. Of those IUCN taxa, only U. crassus is listed as protected on the national level (along with 12 mostly local endemic gastropod species). In comparison with the previous checklist of gastropods by Karaman & Karaman (2007), a total of seven species are added here: Belgrandiella serbica Glöer 2008, Bythinella istoka Glöer & Pešić 2014, B. nonveilleri Glöer 2008, B. pesterica Glöer 2008, Acroloxus lacustris (Linnaeus, 1758), Melanoides tuberculata (O.F. Müller, 1774) and Armiger crista (Linnaeus, 1758). In view of global and regional trends in taxonomy, ecology and invasive biology, an even richer diversity of the Serbian freshwater malocofauna can be expected.